Pathologist’s approach to paediatric and neonatal eosinophilic gastrointestinal disorders - Campora*, Michela; Mastracci*, Luca; Carlin, Luca; Unti, Elettra; Parente, Paola; Fassan, Matteo; Ferro, Jacopo; Errico, Maria Elena; Donofrio, Vittoria; Grillo, Federica (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
Children are not simply miniature adults. The evaluation of their gastrointestinal disorders is therefore different from that in full-grown adults and requires a particular clinical/pathologic approach. Different studies have tried to assess the normal eosinophil distribution in the gastrointestinal tract in adults while very few studies have investigated the paediatric population, consequently complicating the pathologist’s ability in identifying an abnormal number of eosinophils in this setting of patients. When evaluating gastrointestinal tract biopsies with eosinophilia, eosinophilic count must be considered along with other histological features like eosinophil distribution in the gastrointestinal wall, their degranulation, cryptitis and crypt abscesses, other accompanying inflammatory cells, apoptotic bodies, foreign material or microorganisms; these findings, although rarely specific, may be a useful aid for diagnosis. Reports should not include a diagnosis of primary eosinophilic gastrointestinal disorders (EoGID) if clinical data and test results do not rule out other forms of gastrointestinal eosinophilia. A more descriptive definition like “with eosinophilic pattern” should be favoured over a specific diagnosis of “eosinophilic disorder” in order to avoid potential confusion between different entities.